The Effect of Mindfulness-Based Counseling Program on Academic Stress among College Students - Shinta, Dewi; Khan, Razia; Amin, Rafiullah (Yayasan Adra Karima Hubbi, 2025)
Academic stress is a prevalent issue among college students, often leading to negative psychological and academic outcomes. This study aimed to evaluate the effect of a mindfulness-based counseling program in reducing academic stress. A quasi-experimental design with a pre-test and post-test control group was employed, involving 120 college students divided into experimental and control groups. The experimental group participated in an eight-week mindfulness-based intervention, while the control group received no intervention. The results indicated a significant reduction in academic stress levels among participants in the experimental group compared to the control group (p < 0.01). Participants reported improved emotional regulation, concentration, and coping strategies. These findings underscore the efficacy of mindfulness practices in fostering psychological resilience among students. This research contributes to the field by integrating mindfulness techniques into counseling programs specifically tailored for academic stress. The study's limitations include its reliance on self-reported measures and a relatively short follow-up period. Future studies should incorporate longitudinal designs and objective stress indicators to validate the findings further.